Renal disease pathophysiology and treatment: contributions from the rat - Linda J. Mullins; Bryan R. Conway; Robert I. Menzies; Laura Denby; John J. Mullins (The Company of Biologists, 2016)
The rat has classically been the species of choice for pharmacological studies and disease modeling, providing a source of high-quality physiological data on cardiovascular and renal pathophysiology over many decades. Recent developments in genome engineering now allow us to capitalize on the wealth of knowledge acquired over the last century. Here, we review rat models of hypertension, diabetic nephropathy, and acute and chronic kidney disease. These models have made important contributions to our understanding of renal diseases and have revealed key genes, such as Ace and P2rx7, involved in renal pathogenic processes. By targeting these genes of interest, researchers are gaining a better understanding of the etiology of renal pathologies, with the promised potential of slowing disease progression or even reversing the damage caused. Some, but not all, of these target genes have proved to be of clinical relevance. However, it is now possible to generate more sophisticated and appropriate disease models in the rat, which can recapitulate key aspects of human renal pathology. These advances will ultimately be used to identify new treatments and therapeutic targets of much greater clinical relevance.